Hawthorne Revisited: Management and the Worker, its Critics, and Developments in Human Relations in Industry - Gosselin, Émile (Relations industrielles / Industrial Relations, 1959)
The article reviews the book, "Hawthorne Revisited: Management and the Worker, its Critics, and Developments in Human Relations in Industry," by Henry A. Landsberger.